Exposure to Englishes in Listening Classrooms: The Perspectives Of Indonesian ESL Learners - Reni Kusumaningputri (JEELS (Journal of English Education and Linguistics Studies), 2020)
Due to the global scale of English use, English as a lingua franca (ELF) is at play. Given this reality, exposes to different varieties of English rather than a single variety of English, preparing second language learners to Englishes is paramount for readiness to involve in ELF communication. This paper reports on the classroom instruction of exposing college listeners with Englishes via TED talks using a portfolio to find out how they see these varieties and what they can learn from them. Data were from records of portfolio and questions at the end of the instruction. Using general inductive analysis, there were three lessons learned from the instruction. Acknowledgement of many models of English, Englishes can be the ‘right’ English, and Englishes as a marker of identity were lessons observed to appear from the Englishes exposure. The exposes to Englishes also brought about complexities of wholehearted adoption to Indonesian accent. Pedagogical implications for classroom instructions are also made.